Board Gender Diversity and Dividend Payouts in the UK: A Difference-in-Differences Approach - Ashforth, Tyeler M. (2021)
This paper investigates whether board gender diversity does lead to greater dividend payouts for FTSE 100 companies in the UK. The difference-in-differences technique is employed to establish causality and minimise the effects of endogeneity using a panel dataset covering 2014 to 2019. Specifically, the exogenous shock from the June 23rd, 2016, Brexit referendum is used on the treatment group of UK FTSE 100 firms with the control group consisting of German HDAX firms. The empirical results provide no evidence supporting a significant effect of board gender diversity on the size and likelihood of dividend payouts in the UK post-Brexit referendum. Further, only a marginal negative effect of board gender diversity on firm value is found reinforcing the prior results. These conclusions challenge much of the extant literature which suggests a positive relationship between women on boards and firm outcomes.